A Solution for Risk Management of a Distribution Company in the Retail Market - Forough Taki; Ali Shishebori; Ramtin Sadeghi (Majlesi Journal of Electrical Engineering)
In this paper, distributed generations for risk management of a distribution company (DisCo) in the competitive market environment are introduced. The proposed model for this problem considers a stochastic programming framework in the yearly horizon that is to maximize the expected profit considering the uncertainties of the retail market such as the end user demand and the electricity pool price. In this study, the key point is modeling the uncertainties of distributed generations as a reliable source for DisCos. Finally, the approach suggests the optimal resources for procuring the customers' load. Also a basic carbon market is modeled to support the role of renewable energies.